Cognitive Resonant Communication by Internal Speech through Intelligent Bioinformation Systems - Evgeniy Bryndin (Budapest International Research and Critics University, 2023)
A person is simultaneously in a material, ethereal and spiritual environment. It is connected to the material environment by gravity. In the ethereal environment, he is capable of levitation. In the spiritual environment, he is perfected to the likeness of the Creator. A person's thoughts have a spiritual essence. Thinking initiates inner speech, which generates gravitational waves. The research is devoted to communication through internal speech, the direction of the development of new technologies and interdisciplinary research on cognitive communication by internal speech in the ethereal environment at the damage of gravitational waves. The transition to cognitive communication based on natural technology will save resources on digital communication. It will also help solve information interaction problems through the noosphere